1985
DOI: 10.1007/bf00293162
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypomethylation causes an increase in DNase-I sensitivity and an advance in the time of replication of the entire inactive X chromosome

Abstract: We have examined the effect of 5-azacytidine (5-aza-C) induced hypomethylation of DNA on the time of replication and DNase I sensitivity of the X chromosomes of female Gerbillus gerbillus (rodent) lung fibroblast cells. Using in situ nick translation to visualise the potential state of activity of large regions of metaphase chromosomes we show that 5-aza-C causes a dramatic increase in the DNase-I sensitivity of the entire inactive X chromosome of female G. gerbillus cells and this increase in nuclease sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 20 publications
2
42
1
2
Order By: Relevance
“…However to date, the mechanisms of cellular responses of this drug are not well understood. Treatment with 5-aza-CR causes a variety of changes in cells, including decondensation of chromatin (Haaf and Schmidt, 1989), the activation of silenced genes and global genomic hypomethylation (Christman, 2002), and alterations in DNA replication timing (Jablonka et al, 1985), all of which are believed to be consequences of drug-induced demethylation. 5-aza-CR-induced cytotoxicity may be also related to enzyme adduct formation (Juttermann et al, 1994) whereby the incorporation of 5-aza-CR into DNA leads to the irreversible binding of DNMT1 to incorporated 5-aza-CR residues and the rapid loss of DNMT1 activity (Christman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However to date, the mechanisms of cellular responses of this drug are not well understood. Treatment with 5-aza-CR causes a variety of changes in cells, including decondensation of chromatin (Haaf and Schmidt, 1989), the activation of silenced genes and global genomic hypomethylation (Christman, 2002), and alterations in DNA replication timing (Jablonka et al, 1985), all of which are believed to be consequences of drug-induced demethylation. 5-aza-CR-induced cytotoxicity may be also related to enzyme adduct formation (Juttermann et al, 1994) whereby the incorporation of 5-aza-CR into DNA leads to the irreversible binding of DNMT1 to incorporated 5-aza-CR residues and the rapid loss of DNMT1 activity (Christman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…While this appears to be accomplished through a straightforward binary histone modification code, it should be noted that the relationship between histone acetylation levels and replication timing may actually be quite complex (Figs. 2, 3), and other epigenetic signals, such as DNA methylation, could also play a role in this program (Jablonka et al 1985;Hansen et al 2000). It has been suggested that replication timing may merely reflect local transcription, with active regions being early replicating (Gilbert 2002).…”
Section: Histone Modification Controls Replication Timing Genes and Devmentioning
confidence: 99%
“…Hypomethylation caused by aza-C can lead to alteration of gene expression, replication timing, and decondensation of chromatin (14)(15)(16)(17)(18). Significantly, tumor-suppressor genes can be reactivated by aza-C treatment, and synergistic effects have been seen with a histone deacetylase inhibitor (19).…”
Section: Introductionmentioning
confidence: 99%